Longitudinal profile changes in an Anatolian Turkish population - Hamamci, Nihal; Arslan, Seher Gündüz; Şahin, Semra (European journal of orthodontics, 2010)
The goal of this study was to assess longitudinal changes in the facial soft tissue profile in relation to age and gender in young Anatolian Turkish subjects. A total of 30 subjects (15 females and 15 males) with an Angle Class I occlusal relationship and normal antero-posterior (ANB, 2–4 degrees) skeletal relationships were selected from the archive of Dicle University. All subjects were of Anatolian Turkish heritage, and none had any apparent facial disharmony or had undergone orthodontic therapy. Lateral cephalometric radiographs taken at T1 (mean age 8.8 years), T2 (mean age 13.8 years), and T3 (mean age 17.8 years) were separately investigated. Non-gender-specific research was also carried out at the same time periods. In total, 24 measurements were analysed longitudinally. Differences between the genders were determined using independent t-tests. Repeated measures analysis of variance tests were used to evaluate repeated measurements, and paired sample t-tests to compare inside effects between the genders. Significant increases (P < 0.05) were found with age for both females and males. Generally, the increases were greater in males than in females. Nasal prominence increased more than chin prominence, resulting in a tendency to have convex profiles.